Palbociclib for the Treatment of Estrogen Receptor–Positive, HER2-Negative Metastatic Breast Cancer - Morikawa, Aki (Clin Cancer Res, 2015)
Palbociclib is a selective inhibitor of cyclin-dependent kinases 4 and 6 that acts by reducing phosphorylation of the tumor suppressor gene Retinoblastoma. When added to the aromatase inhibitor letrozole in a randomized phase II trial for first-line therapy of estrogen receptor-positive, HER2-negative metastatic breast cancer, palbociclib significantly increased progression-free survival compared to letrozole alone (palbociclib + letrozole: 20.2 months (95% CI 13.8-27.5), letrozole:10.2 months (95% CI 5.7-12.6); hazard ratio 0.49 (95% CI 0.32-0.75), p=0.0004). Based on these results the drug was recently granted accelerated approval by the FDA, and confirmatory studies are ongoing. Since this drug has a rational target in an oncologic pathway, concurrent biomarker development is of interest. In breast cancer, the most useful predictive biomarkers identified thus far are estrogen receptor and HER2 receptor status, although additional studies are ongoing. In this article, we review the development of palbociclib and its use in treatment of hormone receptor-positive metastatic breast cancer in the context of other FDA-approved agents in this setting.